2020
DOI: 10.1002/agm2.12125
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine attenuates vascular smooth muscle cells calcification through mTOR signaling pathway

Abstract: Vascular calcification is increasingly afflicting the aging population, driven by the dysmetabolic milieus of diabetes, chronic kidney disease (CKD), and arterial stiffness. 1-4 Although it has always been considered as an independent predictive factor of cardiovascular events and associated morbidity, the precise relationship between aging and vascular calcification is not well understood. Aging has been demonstrated as a complex multifactorial process, converse to the previous models built on single factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Carnosine is a decisive factor in the formation of atherosclerotic lesions, and it can repress atherogenesis by promoting the removal of aldehydes derived from oxidized lipids ( 33 ). Based on a calcification model of vascular smooth muscle cells (VSMCs), Huang et al ( 34 ) reveals that carnosine can attenuate calcium deposition in a dose-dependent way by reducing expression of osteogenesis-related proteins RUNX2 and BMP2. Compared with normal controls, plasma choline levels are significantly increased in patients with AS, as well as in patients whose aortic valves had neovascularization, calcification, metaplastic ossification, and more severe tissue remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Carnosine is a decisive factor in the formation of atherosclerotic lesions, and it can repress atherogenesis by promoting the removal of aldehydes derived from oxidized lipids ( 33 ). Based on a calcification model of vascular smooth muscle cells (VSMCs), Huang et al ( 34 ) reveals that carnosine can attenuate calcium deposition in a dose-dependent way by reducing expression of osteogenesis-related proteins RUNX2 and BMP2. Compared with normal controls, plasma choline levels are significantly increased in patients with AS, as well as in patients whose aortic valves had neovascularization, calcification, metaplastic ossification, and more severe tissue remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of miR-542-3p in VSMCs plays an important role in the osteogenic transformation of these cells in aging rats and is achieved by targeting BMP-7 ( 68 ). Recently, myostatin was reported to reduce the expression of Runx-2 and BMP-2 in rat VSMCs, operating through the mammalian target of rapamycin (mTOR) signaling pathway and thereby attenuating VSMCs calcification ( 69 ).…”
Section: The Pro-atherosclerotic Properties Of Senescent Vsmcsmentioning
confidence: 99%
“…Carnosine is a dipeptide with antioxidant, anti-inflammatory, and anti-senescence properties [ 77 , 78 ]. Yi and colleagues showed that carnosine inhibited Pi-induced VSMCs calcification by reducing Ca 2+ levels and ALP activity and suppressing the expression of the osteogenic markers Runx2 and BMP-2 [ 79 ]. Carnosine also inhibited the mTOR pathway [ 80 ], which plays a crucial role in the osteoblastic differentiation of VSMCs [ 96 ].…”
Section: Anticalcifying Agentsmentioning
confidence: 99%